The memory of the place: Kolumba Kunstmuseum - Alfaro Lera, José Antonio (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2013)
In September 2007 opened the art museum of the Archdiocese of Cologne, Kolumba Museum. The building stands on the remains of a gothic church destroyed by allied bombing in 1943. Like so many other monuments destroyed in Germany during World War II, is part of a slow process of national recovery of devastated places, than as collective catharsis, begins immediately after the war and expands until today. In the 50s, the ruins were integrated into a memorial garden and a small chapel was built to shelter the Madonna of the Ruins, miraculously intact after the bombing. The protection of the archaeological remains and the ruins of the gothic church, the integration of the modern chapel and the need to harbor the art collection of the Archdiocese, determined the call for an architectural competition in 1997, won by Peter Zumthor. Swiss architect intervention is the last layer of a construction palimpsesto on a sacred space that insists on reborn after the cycles of destruction that ravaged Europe for centuries. A phenomenological approach to the construction site and the activation of the memory that Zumthor achieved with an intensely sensorial architecture is the subject of this paper.